Co-Production dalam Pelayanan Kesehatan: Studi padaPosyandu Nusa Indah 22 - Damayanti Simangunsong; Imam Yudhi Prastya; Chaerey Ranba Sholeh (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Disparities in community attendance at Posyandu health services remain a challenge in community-based health care delivery, including at Posyandu Nusa Indah 22, Kabil Village, Batam City. This study aims to analyze the practice of co-production in the Posyandu program and to identify cadres' contributions in reducing visitation disparities. This research uses a descriptive qualitative approach through the analysis of seven dimensions of co-production, namely actor, reasons, inputs, outputs, phase, means, and context. Data were obtained through interviews, observation, and documentation involving health workers, Posyandu cadres, and community members. The findings show that co-production operates through the involvement of three key actors, namely the government or Puskesmas, cadres, and the community, with cadres playing a central bridging role in mobilizing community participation while supporting health program delivery. Supporting factors include cadres' commitment, Puskesmas support, free services, effective communication, a culture of mutual cooperation, and the implementation of Primary Care Integration (ILP). However, co-production has not run optimally, as community involvement remains concentrated in the implementation stage while participation in planning and evaluation is still limited, constrained by work obligations and low awareness of routine health check-ups. Strengthening health education, cadre capacity, and cross-actor coordination is therefore needed for co-production to run more inclusively and sustainably.